The study of results of learning management on reading words from Mae Kon spelling group using the practice practuce and think pair share cooperative learning techniques of Prathomsuksa 1 pupils - Khotyota, Thitikorn (Journal for Developing the Social and Community, 2023)
The objectives of this research paper were 1) to study the effectiveness of the Think Pair Share Cooperative Learning Practice Form on the subject of reading and spelling for the first graders to be effective according to the 80/80 criteria 2) To compare the learning achievement of grade 1 students before and after learning management. by using the Collaborative Learning Practice Form with Think Pair Share Technique on Reading and Spelling Phrases for Grade 1 students 3) to study the students' satisfaction with learning management. by using the collaborative learning exercise, Think Pair Share technique, on the subject of reading and spelling for the first graders which is obtained by simple sampling There were 29 students. The research tools consisted of the Thai language learning management plan and the cooperative learning principle on the subject of reading and spelling out the mother of grade 1 students. by using the exercises to distribute the spelling with collaborative learning, Think Pair Share technique, an achievement test with a score of Objective Consistency (IOC) ranging from 0.60 - 1.00, with a confidence value of 0.95; and an estimation of satisfaction questionnaire 5. Level: IOC values ​​ranged from 0.60 - 1.00 with a confidence value of 1.00. The statistics used in the data analysis were mean, percentage, standard deviation, and statistical value. The results showed that 1) The results of finding the effectiveness of the exercise on reading and spelling out the parent section of the Think Pair Share cooperative learning technique of Prathomsuksa 1 students found that the efficiency value was E1/E2 = 91.03/90.34, which Higher than the specified criteria is 80/80 2) Comparison of learning achievement on the subject of reading and spelling for the mother section by using the exercise model in conjunction with the Think Pair Share cooperative learning technique for primary school students. In the first year, it was found that the achievement score after school was higher than before. 3) the level of satisfaction with learning management It was found that the reading exercises were used to give the children spelling words in the parent section together with the collaborative learning, Think Pair Share technique for grade 1 students. It was found that at the highest level.